Phenotypic and genetic spectrum of isolated macrodactyly: somatic mosaicism of PIK3CA and AKT1 oncogenic variants - Tian, Wen; Huang, Yingzhao; Sun, Liying; Guo, Yang; Zhao, Sen; Lin, Mao; Dong, Xiying; Zhong, Wenyao; Yin, Yuehan; Chen, Zefu; Zhang, Nan; Zhang, Yuanqiang; et al. (Orphanet journal of rare diseases, 2020)
Isolated macrodactyly is a severe congenital hand anomaly with functional and physiological impact. Known causative genes include PIK3CA, AKT1 and PTEN. The aim of this study is to gain insights into the genetics basis of isolated macrodactyly. We enrolled 24 patients with isolated macrodactyly. Four of them were diagnosed with Proteus syndrome based on skin presentations characteristic to this disease. Targeted next-generation sequencing was performed using patients' blood and affected tissues. Overall, 20 patients carry mosaic PIK3CA pathogenic variants, i.e. p.His1047Arg (N = 7), p.Glu542Lys (N = 6), p.Glu545Lys (N = 2), p.His1047Leu (N = 2), p.Glu453Lys (N = 1), p.Gln546Lys (N = 1) and p.His1047Tyr (N = 1). Four patients who met the diagnostic criteria of Proteus syndrome carry mosaic AKT1 p.Glu17Lys variant. Variant allele frequencies of these mosaic variants obtained through next-generation sequencing range from 10 to 33%. In genotype-phenotype correlation analysis of patients with PIK3CA variant, we found that patients with the macrodactyly of the lower limbs tend to carry PIK3CA variants located in the helical domain (P = 0.005). Mosaic PIK3CA and AKT1 variants can be found in all of our samples with isolated macrodactyly. Insights into phenotypic and genetic spectrum of isolated macrodactyly may be helpful in perusing a more precise and effective management of isolated macrodactyly.